Pemphigus vegetans with isolated involvement of the nose and chest: rare variant of pemphigus vulgaris - Raisa Ilena Caranhas Feitoza; Mônica Santos; Maria da Conceição Almeida Schettini; Silvana de Albuquerque Damasceno Ferreira (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Pemphigus vulgaris is chronic bullous disease that manifests as bullae and erosions of skin and mucosas, with intraepidermal suprabasal cleft formation seen in the histological examination. It has a rare variant called pemphigus vegetans, where vesicles and bullae are replaced by pustular, verrucous and hyperpigmented lesions, mainly in skin folds. The treatment is similar to that for classic pemphigus vulgaris. The authors present an exuberant case of pemphigus vegetans, covering the nose and chest exclusively, without oral or flexural lesions.